1998
DOI: 10.1183/09031936.98.11020400
|View full text |Cite
|
Sign up to set email alerts
|

Integrin dependent migration of lung cancer cells to extracellular matrix components

Abstract: Since tumour progression is dependent on the ability of malignant cells to interact with the extracellular matrix (ECM), we have investigated the significance of beta1 and beta3 integrins for migration of lung cancer cells to components of the ECM. In an in vitro hapto- and chemotactic assay system, five cell lines representing the major types of lung cancer were examined: adenocarcinoma (WART); squamous cell carcinoma (U-1752); small cell lung cancer (SCLC) (U-1906, 054 A) and large cell lung cancer (LCLC) (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In contrast to the study by Koukoulis et al [26], who described a variable intense reaction for αv in SCCs and ACs similar to that of the bronchial epithelium [26] and no staining for β3 in immunohistology, we could demonstrate that variable expression in αvβ3 using reverse-transcription PCR and fluorescenceactivated cell sorter analysis in lung tumor cell lines and using immunohistology in lung carcinomas. Additionally, Bredin et al [8] revealed that two of five lung cancer cell lines express the β3 chain. Furthermore, we demonstrated that both molecules were sometimes co-localized in the same tumor cell in ADAM15 as well as in αvβ3 integrinpositive lung tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the study by Koukoulis et al [26], who described a variable intense reaction for αv in SCCs and ACs similar to that of the bronchial epithelium [26] and no staining for β3 in immunohistology, we could demonstrate that variable expression in αvβ3 using reverse-transcription PCR and fluorescenceactivated cell sorter analysis in lung tumor cell lines and using immunohistology in lung carcinomas. Additionally, Bredin et al [8] revealed that two of five lung cancer cell lines express the β3 chain. Furthermore, we demonstrated that both molecules were sometimes co-localized in the same tumor cell in ADAM15 as well as in αvβ3 integrinpositive lung tumors.…”
Section: Discussionmentioning
confidence: 99%
“…We further tested whether the supernatants from the VAPϩ/MICAϩ cell cultures from patients with WG and healthy control subjects had the ability to induce neutrophil migration using a 48-well Boyden chamber (Neuro Probe, Gaithersburg, MD). Neutrophils were isolated from 10 normal individuals, and the assay was performed as described earlier (27,28). Migrated cells were counted in four randomly chosen microscope fields (ϫ40) in a blinded manner, and the average was determined.…”
Section: Functional Analysis Of Vap-1ϩ/micaϩ Cellsmentioning
confidence: 99%
“…CD9 associates with b1 integrins but not with N-CAM SCLC reportedly expresses adhesion proteins, b1 integrins and N-CAM, and both of these molecules are likely to regulate motility and metastasis of SCLC (Scheidegger et al, 1994;Bredin et al, 1998). To explore the mechanisms involved in the reduction of OS3-R5-pZCD9 motility, coimmunoprecipitation experiments using MoAbs against these molecules were performed (Figure 4b,left panel).…”
Section: Ectopic Expression Of Cd9 Into Os3-r5 Reduces Cell Motility mentioning
confidence: 99%